2018
DOI: 10.3389/fncel.2018.00317
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of MSC-Derived Exosomes in Neuroplasticity in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common type of dementia affecting regions of the central nervous system that exhibit synaptic plasticity and are involved in higher brain functions such as learning and memory. AD is characterized by progressive cognitive dysfunction, memory loss and behavioral disturbances of synaptic plasticity and energy metabolism. Cell therapy has emerged as an alternative treatment of AD. The use of adult stem cells, such as neural stem cells and Mesenchymal Stem Cells (MSCs) from bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 171 publications
1
105
0
1
Order By: Relevance
“…The tangles also contain small pieces of microtubules, and indeed, due to the loss of function of the tau protein, the microtubule dynamics and function are impaired in both anterograde and retrograde trafficking along the axons of molecules/complexes/organelles. As a consequence, in a process lasting many years, cortical neurons and synapses are lost in brain areas involved in memory and learning, especially the prefrontal cortex and hippocampus [256,257]. Eventually β-amyloid plaques and neurofibrillary tangles may also extend to other brain formations [258] such as limbic and association areas [259].…”
Section: Evs In Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The tangles also contain small pieces of microtubules, and indeed, due to the loss of function of the tau protein, the microtubule dynamics and function are impaired in both anterograde and retrograde trafficking along the axons of molecules/complexes/organelles. As a consequence, in a process lasting many years, cortical neurons and synapses are lost in brain areas involved in memory and learning, especially the prefrontal cortex and hippocampus [256,257]. Eventually β-amyloid plaques and neurofibrillary tangles may also extend to other brain formations [258] such as limbic and association areas [259].…”
Section: Evs In Neuropathologymentioning
confidence: 99%
“…Eventually β-amyloid plaques and neurofibrillary tangles may also extend to other brain formations [258] such as limbic and association areas [259]. As the disease progresses, aggregates of Aβ are also found in motor areas, CSF, and even in regions not directly belonging to brain, such as the eyes [257].…”
Section: Evs In Neuropathologymentioning
confidence: 99%
“…But it remains unclear why the reported studies demonstrated much less efficacy because we could consistently repeat our results in multiple settings, even when using MSCs passaged up to 30. Paracrine effects play an important role in mesenchymal stem cell transplantation clinical trials [28][29][30]. Some studies have shown MSCs, especially UC-MSC, to express preferentially secreted factors related to neuroprotection, neurogenesis, and angiogenesis [31][32][33].…”
mentioning
confidence: 99%
“…Neurodegenerative conditions are of special interest due to their affect on cognitive functions. Alzheimer's disease (AD) is an elaborated neurodegenerative condition, caused by β-amyloid peptide (Aβ) accumulation outside neurons and neurofibrillary tangles (NFT) consisting of hyperphosphorylated tau protein in cells [69]. Another neurodegenerative disorder is amyotrophic lateral sclerosis (ALS) resulting in general in impairment of human motor system and death predominantly because of respiratory failure.…”
Section: Neurological Diseasesmentioning
confidence: 99%